An Exploratory Study for Proteomic-Based Markers of Joint Pain and Chronic Back Pain - Schillemans, Tessa; Rönnegård, Ann Sofie; Assimes, Themistocles L.; Peterson, Magnus; Wändell, Per; Lind, Lars; Ärnlöv, Johan (European Journal of Pain, 2025)
Background: Joint pain and chronic back pain are highly prevalent in the aging population and have a large impact on life quality. As the underlying mechanisms are not fully understood, this exploratory cross-sectional study aimed to discover proteins and pathways associated with these two pain conditions in Swedish 70-year-old men. Methods: Plasma proteins (n = 720) were measured in participants from the Uppsala Longitudinal Study of Adult Men (ULSAM; n = 931) using Olink target panels. Participants self-reported current joint pain or continuous back pain during the past year. We used logistic regression with multiple testing adjustments and RIDGE regression (selecting ~10% highest-ranking proteins) to identify proteins associated with either joint or chronic back pain, which were then investigated for clusters and pathway enrichments. Results: Out of 931 subjects with protein data, 131 reported joint pain and 31 reported chronic back pain. We identified 19 (significant after multiple testing adjustment) and 25 (nominally significant) highest-ranking proteins associated with joint and chronic back pain, respectively. Enriched pathways included immune responses, inflammation, lipid, coagulation and rheumatoid arthritis pathways. Similar pathways were found for both joint and chronic back pain, even though only two proteins were associated with both these pain conditions. Conclusions: This exploratory proteomics study provides support for systemic inflammation as a common underlying mechanism for joint and chronic back pain. Although similar pathways were found for both pain conditions, the selected proteins differed. Nevertheless, caution is advised due to low sample size and validation in larger studies including both women and men is needed. Significance Statement: Logistic and RIDGE regression analyses indicated that joint pain and chronic back pain were associated with different proteins, which were enriched for similar inflammatory pathways.
Publisher Copyright: © 2025 The Author(s). European Journal of Pain published by John Wiley & Sons Ltd on behalf of European Pain Federation - EFIC ®.